Punishment or mercy? Tripartite game between the State, offenders, and victims in China’s environmental crime governance - Xinrui Zhang; Jiashu Zhang (Humanities & Social Sciences Communications)
Abstract China is attempting restorative justice reforms in environmental crime governance. However, a discrepancy remains between the ideal and the reality of environmental restorative justice (ERJ), particularly in balancing mercy or punishment. This study explores the strategies of the State, offenders, and victims in China’s environmental crime governance and develops a three-party evolutionary game model to analyze these interactions. Analysis of evolutionary stability identifies four potential scenarios that align with legal theory and practice during the ERJ reform process: Compromise justice, Retributive justice, Reparative justice, and Restorative justice. The simulation results based on environmental crime governance data from 2019 to 2023 indicate that current reforms are primarily oriented towards achieving reparative justice, where environmental restoration outcomes rely on punitive pressure from the State on offenders. To foster a more effective transition towards ERJ, we suggest the State maintain punishment in a moderate level through an environmental punitive compensation system. At the same time, social forces should be encouraged to participate in environmental crime governance.